Simplified Method for Calculation of the Joule-Thomson Coefficient at Natural Gas Flowrate Measurement - Yevhen Pistun; Fedir Matiko; Oleh Masnyak (Energy Engineering and Control Systems)
This work deals with measurement of natural gas flowrate and volume by means of pressure differential devices. The existing methods for calculation of Joule-Thomson coefficient to be applied in pressure differential flowmeters are analyzed in the paper. A new method which uses a simplified set of parameters of gas composition, namely the density at standard conditions, the molar content of nitrogen and carbon dioxide, is developed by the authors. This method provides the possibility to calculate the Joule-Thomson coefficient within the pressure range from 0.1 MPa to 15.0 MPa and the temperature range from 250 K to 350 K. It was defined that for natural gas with density at standard conditions up to 0.75 kg/m3 and contents of nitrogen and carbon dioxide up to 5 % of each component, the relative error of the values derived according to the new developed method do not exceed 3.0 % in the specified ranges of temperature and pressure. The application of this method in calculators of flowrate and volume of natural gas will help to reduce the systematic error of flowrate and volume measurement caused by the distinction of gas temperature in the place of measurement downstream of primary device from gas temperature upstream of primary device.